ANALISIS GAYA BAHASA (MAJAS) DAN MAKNA PADA CERPEN “TOMBAK SANG PENENUN“ KARYA BENNY ARNAS (KAJIAN STILISTIKA) - Fadhilah, Umu (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
This research problem was about language style and figure of speech in a short story and analyze about short story meaning of